Social differentiation and local government in Pella, a rural coloured area in Great Bushmanland - Klinghardt, Gerald Philip (Social Anthropology, 2024)
This dissertation has as its focus structural differentiation in the Rural Coloured Area (or Reserve) of Pella in Great Bushmanland in the North-western Cape Province, within the context of local government over the past hundred years. In an attempt to synthesise an analysis of constitutional structures with one of political practices and activities, a diachronic approach has been adopted in order to demonstrate continuities of form between missionary and bureaucratic systems of local government and the manner in which structures of social differentiation and government have emerged from continuous processes of class and ethnic struggle. For this purpose it is essential to take a long time perspective so as to examine the role of power in processes of intergroup relationships. The authority structure is treated as a dependent variable in the political process and the decision-making system is used to depict the dynamic nature of the political system through time. Set against the background of the system of White capitalist domination in South Africa, the class struggle is shown to have been conducted in terms of ethnicity, with the elite of a ruled class exploiting avenues of available political power in order to replace a ruling class and then being itself transformed into a ruling class. The apparent success of the modified and renewed Nationalist policy in creating a new class structure in South Africa together with an increasing emphasis importance of local government can be seen to have in fact encouraged resistance on the part of conservative forces at the local level. This could lead to difficulties with the process of administration in the future.